GE_GERICHTE C/30531/2005 vom 23. Mai 2016 - GE Cour de justice (2016)
DROIT TRANSITOIRE ; TRIBUNAL DES BAUX ; COMPÉTENCE ; CONSTATATION DES FAITS ; SOUS-LOCATION ; INTERPRÉTATION(SENS GÉNÉRAL) ; RESTITUTION ANTICIPÉE | LPC.436.1; CO.18; CO.262.1; CO.264;